2011
DOI: 10.1111/j.1558-5646.2011.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recurrent Selfing on Inbreeding Depression and Mating System Evolution in an Autopolyploid Plant

Abstract: Genome duplication resulting in polyploidy can have significant consequences for the evolution of mating systems. Most theory predicts that self-fertilization will be selectively favored in polyploids; however, many autopolyploids are outcrossing or mixedmating. Here, we examine the hypothesis that the evolution of selfing is restricted in autopolyploids because the genetic cost Inbreeding depression (δ), the reduced fitness of inbred offspring compared to outbred offspring, is a dominant selective force gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 69 publications
4
27
0
Order By: Relevance
“…Of the species for which we were able conclusively to determine ploidy level, relatively more polyploid than diploid species were capable of GS (82% of polyploids and only 54% of diploids, although this is based on only 11 species known to be polyploid; Table 1). In accord with the frequent suggestion in the literature that polyploids should be more tolerant of selfing than their diploid relatives (see, e.g., Stebbins, 1950;Grant, 1956;Soltis & Soltis, 1987;Haufler, 1989;Masuyama & Watano, 1990;Barringer, 2007;Ozimec & Husband, 2011), we did see higher average isolate potentials in polyploid compared with diploid species, but the difference did not reach statistical significance (Fig. 6b).…”
Section: Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…Of the species for which we were able conclusively to determine ploidy level, relatively more polyploid than diploid species were capable of GS (82% of polyploids and only 54% of diploids, although this is based on only 11 species known to be polyploid; Table 1). In accord with the frequent suggestion in the literature that polyploids should be more tolerant of selfing than their diploid relatives (see, e.g., Stebbins, 1950;Grant, 1956;Soltis & Soltis, 1987;Haufler, 1989;Masuyama & Watano, 1990;Barringer, 2007;Ozimec & Husband, 2011), we did see higher average isolate potentials in polyploid compared with diploid species, but the difference did not reach statistical significance (Fig. 6b).…”
Section: Researchsupporting
confidence: 91%
“…Future data collection efforts should focus on including groups of species with polyploid series and those found to be exclusively selfing, in order to improve our understanding of the relationship between ploidy level and selfing capacity in ferns. It has also been suggested that as polyploid genomes 'diploidize' following whole-genome duplication, and return to disomic inheritance and diploid expression patterns (Dodsworth et al, 2016), the fitness of selfed progeny may deteriorate and mating systems may also evolve, reverting to mixed mating or outcrossing strategies (Husband et al, 2008;Ozimec & Husband, 2011). Assessing mating systems in polyploids of known age could help to test this assertion.…”
Section: Researchmentioning
confidence: 99%
“…In response to population bottlenecks, tetraploids sometimes expressed higher inbreeding depression than is found in much larger populations at equilibrium (Fig. ; Ronfort ; Ozimec and Husband ). This likely occurred because of random selfing and mating between related individuals in small populations.…”
Section: Discussionmentioning
confidence: 96%
“…A persistent question has been whether polyploidy should be associated with increased rates of self‐fertilization in flowering plants (Stebbins ; Levin ; Lande and Schemske ; Ronfort ; Miller and Venable ; Mable ; Rausch and Morgan ; Barringer ; Robertson et al. ; Ozimec and Husband ). Two major hypotheses have been argued to support such an association.…”
Section: Discussionmentioning
confidence: 99%
“…In fireweed, synthetic neopolyploids have no detectable inbreeding depression [Husband et al, 2008], suggesting that selfing, not outcrossing, would be favored, unless the magnitude of inbreeding depression increases over successive generations of selfing [Miller and Venable, 2000]. The limited evidence available is in support for this possibility [Ozimec and Husband, 2011], but more study is needed.…”
Section: Wgd Promotes Evolution Of Gender Dimorphism Via Mating Systementioning
confidence: 84%